1983
DOI: 10.1080/00207238308710074
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals in Indian coals and corresponding fly‐ash and their relationship with particulate size

Abstract: Pulverised coal and corresponding fly-ash collected from the stack precipitator of thermal power plants were analysed for eight heavy metals. Fly-ash was separated into various sized fractions which were then chemically characterized. The fly-ash contained higher concentrations of heavy metals with respect to their coal. Except in the case of Pb, Cd and Co, the heavy metals were more concentrated in the <53 µm than in the >150 µm fraction. For the probable contribution of these metals to atmospheric emission a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 6 publications
(5 reference statements)
0
11
0
Order By: Relevance
“…These values are higher than this work's values for TSP, PM 10 and PM 2.5 . The results show that Ni concentrations are lower at road junctions than near residential and industrial sites since Ni is produced in the combustion of coal (Fuleka et al 1983;Dzubay et al 1982;Stevens et al 1984;Pirrone et al 1996). Van Grieken et al (1982) reported Ni levels of 0.012 μg m −3 for Recife (Brazil) and Rio de Janeiro (Brazil), 0.034 μg m −3 for US Urban and 0.027 μg m −3 for Washington.…”
Section: Nickelmentioning
confidence: 91%
See 4 more Smart Citations
“…These values are higher than this work's values for TSP, PM 10 and PM 2.5 . The results show that Ni concentrations are lower at road junctions than near residential and industrial sites since Ni is produced in the combustion of coal (Fuleka et al 1983;Dzubay et al 1982;Stevens et al 1984;Pirrone et al 1996). Van Grieken et al (1982) reported Ni levels of 0.012 μg m −3 for Recife (Brazil) and Rio de Janeiro (Brazil), 0.034 μg m −3 for US Urban and 0.027 μg m −3 for Washington.…”
Section: Nickelmentioning
confidence: 91%
“…Lead levels were found to increase with decrease in particle size, with the average in PM 10 and PM 2.5 being 0.166 and 0.185 μg m −3 respectively. This shows that combustion is the major source since Lead from combustion is associated with fine particles (Fuleka et al 1983;Dzubay et al 1982;Stevens et al 1984). The WHO annual Lead guideline limit is 0.5 μg m −3 , which is the same as the UK-EU guideline limit.…”
Section: Leadmentioning
confidence: 93%
See 3 more Smart Citations